2018
DOI: 10.1007/s00223-018-0466-5
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mass Development in Childhood and Its Association with Physical Activity and Vitamin D Levels. The CHAMPS-Study DK

Abstract: This longitudinal study examined associations of bone mass with physical activity and vitamin D level over more than 6 years through puberty. A total of 663 participants (320 boys) with mean age 9.6 years at baseline (10-17 years at follow-up), underwent dual energy X-ray absorptiometry, anthropometry and blood samples for vitamin D at least twice during the study period (with three possible time-points). Physical activity was assessed using accelerometers at follow-up. A positive association was found between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The Rønne et al's. study 31 meta-analyzed here and the aforementioned Metcalf et al's study 40 underpin the notion that greater attention should be placed on promoting high-impact VPA throughout adolescence and emerging adulthood to maximize bone strength and reduce fracture risk. Indeed, Ivuškāns et al 45 also found that increases in VPA during a 12-month period favors bone mineral acquisition in peripubertal boys.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The Rønne et al's. study 31 meta-analyzed here and the aforementioned Metcalf et al's study 40 underpin the notion that greater attention should be placed on promoting high-impact VPA throughout adolescence and emerging adulthood to maximize bone strength and reduce fracture risk. Indeed, Ivuškāns et al 45 also found that increases in VPA during a 12-month period favors bone mineral acquisition in peripubertal boys.…”
Section: Discussionmentioning
confidence: 67%
“…A total of 3612 potentially relevant articles were identified, and, after screening for duplicates, 601 full-text studies were assessed for inclusion after checking titles and abstracts. Finally, 23 studies met the eligibility criteria and were included in the systematic review 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 and 21 in the meta-analysis. The reasons for exclusion based on full texts are reported in Supplementary Material 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While some authors claimed a decrease in bone mass relative to body weight [46], others did not document significant differences in bone mineral density [47] or showed an increase in body mass and bone size in obese children, adolescents and adults. Increased bone mass and density observed in obese individuals is postulated to be a response to greater mechanical load, direct influence of leptin or enhanced enzymatic activity of aromatase [48,49]. Nevertheless, obesity markedly increases the risk of bone fractures in children [50].…”
Section: Effect Of Vitamin D Supplementation On Bone Mineral Density mentioning
confidence: 99%
“…The development of bone mineral density (BMD) and content (BMC) during childhood and adolescence is substantial and may attenuate the incidence and effects of osteoporosis later in life (1). Recent study assessed 663 Danish students over 6 years from childhood to adolescence and found positive associations between the level of physical activity and bone health (2). Systematic reviews have shown that physical activity, as well as weight-…”
Section: Introductionmentioning
confidence: 99%